Depression, Depressive Somatic or Nonsomatic Symptoms, and Function in a Primarily Hispanic Chronic Pain Population. (1st December 2012) - Robinson, Kristynia M.; Monsivais, Jose J.
Abstract : Chronic pain and depression are two major causes of disability. Comorbidity decreases psychosocial and physical functioning while increasing economic burden. The prevailing belief that Hispanics somaticize depression may hinder the diagnostic process and, thus, may impact outcomes. The purpose of this study was to explore the relationships among depression and depressive symptoms (somatic or nonsomatic) and function in chronic pain sufferers residing along the USA-Mexico border. Like other studies, as level of depression increased, level of pain increased and level of functioning decreased. So much so that almost a quarter of the participants reported moderate-to-severe depression, and another quarter of the participants reported suicidal ideation independent of depression or treatment. Unlike other published reports, we used a sample of chronic pain patients who received individualized, multimodal pain treatment. Compared to our previous work in a similar population, pain intensity and suicidal ideation were lower in this study. A plausible explanation is the use of antidepressants as adjuvant treatment for pain. Regardless of gender or ethnicity, persons with chronic pain will disclose symptoms of depression when appropriate tools are used to collect the data. Implications for future research and clinical practice are discussed.